SPEAKING TEACHING STRATEGIES BY SECONDARY SCHOOL ENGLISH TEACHER - Pandoyo Situmorang; Valews Nopatri L Purba; Listra Sitohang; Erikson Saragih (STKIP PGRI Jombang, 2022)
The research aims to find out the strategies used by teachers in teaching speaking to students in secondary school and teachers’ perception about the method. This study involved ten English teachers at several secondary schools in North Sumatra. To collect the data, researchers use qualitative descriptive methods by distributed questionnaires as research instruments using the google form platform. This research was conducted to find and identify the teachers’ strategies in teaching speaking. Research indicates that the strategies used by the English teacher were information gap, communicative language by real life situation, brain storming, picture storming, discussion, story-telling, role-play, daily integration in learning process, speech and games. Whereas the teacher's response to the strategy produces a positive attitude because their perception answers that the strategy they used was satisfying and effective to help students to improve their speaking skills. The results of the study also reveal that the teachers’ strategies are essential to improving students' willingness to study at school. Thus the teacher strategy is the key to success in teaching. The results of this study provide a full description of teaching practice, and the assessment employed by the teacher. From this research, it is suggested that teachers use speaking teaching strategies by paying attention to steps to perform the method.